An Evaluation of Value at Risk Models in Chinese Stock Market - Xiao, Ying (2013)
The aim of this article is to examine the predictive performance of VaR model in Chinese stock market and try to find the rational choice of models for China. In order to achieve this goal, Historical simulation approach, Bootstrapped HS, Hull White method, parametric approach with volatility adjustment, Generalized extreme value theory and Peaks-over-threshold approach are applied to the Shanghai Stock Exchange Composite Index (SSECI) and Shenzhen Stock Exchange Composite Index (SZSECI) to estimate the one-day VaR. Then, two backtesting method-Kupiec test and the Conditional Coverage test are carried our to test the validity of these models. It could be concluded that the Hull White approach and the parametric method with volatility adjustment tend to be the proper models for Chinese stock market.